2015
DOI: 10.3389/fonc.2015.00231
|View full text |Cite|
|
Sign up to set email alerts
|

Ionizing Particle Radiation as a Modulator of Endogenous Bone Marrow Cell Reprogramming: Implications for Hematological Cancers

Abstract: Exposure of individuals to ionizing radiation (IR), as in the case of astronauts exploring space or radiotherapy cancer patients, increases their risk of developing secondary cancers and other health-related problems. Bone marrow (BM), the site in the body where hematopoietic stem cell (HSC) self-renewal and differentiation to mature blood cells occurs, is extremely sensitive to low-dose IR, including irradiation by high-charge and high-energy particles. Low-dose IR induces DNA damage and persistent oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 66 publications
0
14
0
1
Order By: Relevance
“…X-rays can cause the transient induction of hematopoietic stem cell (HSC) apoptosis due to their high sensitivity [ 31 ]. In addition, almost all the blood cells, including the lymphoid and myeloid lineages, are extremely sensitive to X-rays [ 32 ]. In this study, we found that osteoclasts, which originated from radiosensitive HSCs, also showed high sensitivity to X-rays, in both progenitors and differentiating cells.…”
Section: Discussionmentioning
confidence: 99%
“…X-rays can cause the transient induction of hematopoietic stem cell (HSC) apoptosis due to their high sensitivity [ 31 ]. In addition, almost all the blood cells, including the lymphoid and myeloid lineages, are extremely sensitive to X-rays [ 32 ]. In this study, we found that osteoclasts, which originated from radiosensitive HSCs, also showed high sensitivity to X-rays, in both progenitors and differentiating cells.…”
Section: Discussionmentioning
confidence: 99%
“…For HSCs, the impact of IR reveals conflicting results. On the one hand, IR is reported to cause apoptosis in hematopoietic stem cells, when they are exposed to the low doses of high energy and high charge radiation that are relevant in space travel [ 125 ]. On the other hand, Li et al reported that very low doses of X-rays act as stimulants of hematopoietic progenitor cells, as their proliferation and mobilization was increased in an animal study [ 126 ].…”
Section: The Influence Of Ir On the Bone Microenvironmentmentioning
confidence: 99%
“…Both low‐dose and high‐dose radiation treatment regimens result in bone loss, mainly due to increase in osteoclast function, and increases in DNA damage and cellular apoptosis of the bone lineage cells . Several studies suggest that bone marrow cells of the hematopoietic lineage are the most sensitive to radiation damage . Cells that are responsible for maintaining bone homeostasis, such as osteoblasts, osteocytes, and mesenchymal stem cells (MSCs), undergo varying degrees of DNA damage and apoptosis, with osteoblasts being more sensitive and MSCs more resistant.…”
Section: Introductionmentioning
confidence: 99%